Proceedings of the 2014 ACM SIGSAC Conference on Computer and Communications Security 2014
DOI: 10.1145/2660267.2660269
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Large Groups of Active Malicious Accounts in Online Social Networks

Abstract: The success of online social networks has attracted a constant interest in attacking and exploiting them. Attackers usually control malicious accounts, including both fake and compromised real user accounts, to launch attack campaigns such as social spam, malware distribution, and online rating distortion.To defend against these attacks, we design and implement a malicious account detection system called SynchroTrap. We observe that malicious accounts usually perform loosely synchronized actions in a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
173
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(174 citation statements)
references
References 23 publications
1
173
0
Order By: Relevance
“…This observation is in line with early findings on political campaigns orchestrated by social bots, which exhibited not only peculiar network connectivity patterns but also enhanced levels of coordinated behavior. 28 The idea of leveraging information about the synchronization of account activities has been fueling many social bot detection systems: frameworks like CopyCatch, 4 SynchroTrap, 10 and the Renren Sybil detector 37,42 rely explicitly on the identification of such coordinated behavior to identify social bots.…”
Section: Crowdsourcing Social Bot Detectionmentioning
confidence: 99%
“…This observation is in line with early findings on political campaigns orchestrated by social bots, which exhibited not only peculiar network connectivity patterns but also enhanced levels of coordinated behavior. 28 The idea of leveraging information about the synchronization of account activities has been fueling many social bot detection systems: frameworks like CopyCatch, 4 SynchroTrap, 10 and the Renren Sybil detector 37,42 rely explicitly on the identification of such coordinated behavior to identify social bots.…”
Section: Crowdsourcing Social Bot Detectionmentioning
confidence: 99%
“…<0.0001), then we may claim with a high certainty that coordination is taking place. The suspect string is typically identified by a manual investigation [5] or by automatically applying a clustering algorithm [2][1].…”
Section: Simulating Repetitions In Textmentioning
confidence: 99%
“…They observed that malicious accounts usually perform loosely synchronized actions in a variety of social network contexts. 10 …”
Section: Social Behavior-based Modelsmentioning
confidence: 99%